The interior of the Dutch Reformed church at Britsum (Bulletin KNOB, 2000)
Until its restoration the church at Britsum held two canopied, oak wood Lord's seats: one from the middle of the 17th century belonging to the Burmania family opposite the pulpit from 1667 also donated by this family. Around 1700 the Lord's seat was made for the Van Wyckel family. The original position of this seat is not clear; its transfer is probably connected with its purchase by the church wardens in 1825, when the oak-wood was also painted.The seats are in line with the reformational, whitewashed furnishing of the church and are related to the powerful owners of manors no longer existing in the village. The seats also have a spatial relation with the still present tombs and burial vaults and the elaborately-tooled bluestone ledgers, memorizing the renowned residents of the manors, who were also patrons of the church. They are protected pieces of furniture showing the use of the church in the course of a few centuries.These elements and the families who donated them are indispensable links between the unknown start of the church in the 13th century and contemporary use under supervision of the Foundation Alde Fryske Tsjerken (Old Frisian Churches).